Estudo e caracterização de composições de coque e fibras vegetais (bagaço de cana e madeira) para aplicação na produção de briquetes - Franco, André Juliano (2011)
"Green" petroleum coke is a solid product, obtained from the cracking of heavy residual oils in the waste conversion units called delayed coking units (UCR). The market for application of "green" coke is very broad, perhaps regarded as the product (derived directly from oil) with the greatest potential for industrial use, as in the metallurgical area (fuel or reducer), obtaining refractory crucibles, sintered parts, coating equipment, composition of amber glass, solid fuels. Due to its high calorific value, from 8200 to 8600 kcal/kg, this byproduct of oil is widely used as a source of energy in industries. This study aimed to the blending of petroleum coke fines with natural fibers (eucalyptus and sugarcane bagasse) and subsequently obtains briquettes through compression molding. Thus, it was hoped to obtain a product with a higher calorific value compared with briquettes formed only by vegetable fibers and additionally reduce partly the consumption of materials from non-renewable sources (petroleum coke) to obtain briquettes. The raw materials used were fines of petroleum coke and eucalyptus fibers and sugarcane bagasse .. The proportions of mixtures of fines of petroleum coke and vegetable fibers were: 100% coke fines, 75/25, 50/50, 25/75 and 100% vegetable fibers. The mixtures had their moisture standardized between 10% and 12% and the force used to perform the compaction was 12t. To make the compression it was used a cylindrical stainless steel cast of 9.62 cm2 and a hydraulic press of parallel plates type. The briquettes molded with the ratio 25/75 and 50/50 coke/fibers presented, visually, good compaction and proper agglomeration. It was obtained also the formation of briquettes made of 100% petroleum coke, but they presented themselves fragile. However, for blends 75/25 coke/fibers was not possible to obtain briquettes, probably due to compaction is not adequate. Samples of all produced briquettes were analyzed for gross calorific value (GCV). The briquettes compounded of 50/50 coke/eucalyptus and coke/bagasse showed an increase of approximately 50% in the GCV when compared to those found for the briquettes made from 100% plant fibers. It was doner diametral compression tests for the briquettes and most of them showed characteristics of relatively brittle materials with low strain values. The briquettes compounded of 100% petroleum coke showed the lowest values of stress and strain. For the briquettes compounded of coke/ eucalyptus was observed decreasing behavior of the variables as the concentration of coke increased. For the briquettes compounded of coke/sugar cane bagasse, occurred an increase in the values of variables after the addition of coke.